Objective assessment of surgeon’s psychomotor skill using virtual reality module - Siti Nor Zawani Ahmmad; Eileen Su Lee Ming; Yeong Che Fai; Suneet Sood; Anil Gandhi; Nur Syarafina Mohamed; Hisyam Abdul Rahman; Etienne Burdet (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This study aims to identify measurable parameters that could be used as objective assessment parameters to evaluate surgical dexterity using computer-based assessment module. A virtual reality module was developed to measure dynamic and static hand movements in a bimanual experimental setting. The experiment was conducted with sixteen subjects divided into two groups: surgeons (N = 5) and non-surgeons (N = 11). Results showed that surgeons outperformed the non-surgeons in motion path accuracy, motion path precision, economy of movement, motion smoothness, end-point accuracy and end-point precision. The six objective parameters can complement existing assessment methods to better quantify a trainee’s performance. These parameters also could provide information of hand movements that cannot be measured with the human eye. An assessment strategy using appropriate parameters could help trainees learn on computer-based systems, identify their mistakes and improve their skill towards the competency, without relying too much on bench models and cadavers.